The Implementation of Tax Monitoring System in Local Tax Collection in Sidoarjo District: Implementasi Tax Monitoring System (Taxmon) dalam Pemungutan Pajak Daerah di Kabupaten Sidoarjo - Listiawan, Hermadi; Salman, Radian (Universitas Muhammadiyah Sidoarjo, 2024)
This article aims to explain and analyze the implementation of tax monitoring system to local tax collection in Sidoarjo Regency. The electronic collection of local taxes is a strategy utilized by Sidoarjo Regency to enhance efficiency, effectiveness, and transparency in collecting local taxes, one of them is Tax Monitoring System. This writing reviews the benefits and impacts of the implementation adopted by the local government in implementing tax monitoring system, the advantages of it, and the resulting effects on the local tax revenue of Sidoarjo Regency. Highlights : Enhanced Efficiency: The Tax Monitoring System in Sidoarjo Regency streamlines tax collection processes, reducing manual efforts and expediting transactions. Increased Transparency: This system promotes accountability and transparency in local tax operations, building trust among taxpayers. Revenue Impact: The implementation of the Tax Monitoring System has positively influenced the local tax revenue, indicating improved compliance and collection rates. Keywords : Implementation, Local Tax Revenue, Electronicization, Tax Collection, Efficiency